Analysis of application possibilities of short-circuit effects in metal coating technologies - Miljojkovic, Jasmina; Simunovic, Goran; Vukelić, Đorđe; Tadic, Branko (Journal of Production Engineering, 2019)
Short-circuit effects are well known and widely used in various technologies, ranging from arc welding to latest research on the application of short-circuit effects in 3D printing technologies. The paper presents the results of the research related to the analysis of application possibilities of short-circuit effects in metal coating technologies. In addition to the literature review, the paper presents theoretical background and results of preliminary experimental research.